The role of Earth Observation (EO) technologies in supporting implementation of the Ramsar Convention on Wetlands - MacKay, H.; Finlayson, C. Max; Fernández Prieto, D.; Davidson, N.; Pritchard, D.; Rebelo, Lisa-Maria (Elsevier, 2009)
Over one hundred wetland specialists and Earth Observation experts from around the world gathered at the European Space Agency's 'GlobWetland Symposium: Looking at wetlands from space' in Frascati, Italy, from 19 to 20 October, 2006. The aim of the Symposium was to stimulate discussion between the two communities by reviewing the latest developments in Earth Observation (EO) for the inventory, assessment and monitoring of wetlands and identify key scientific, technical and policy-relevant challenges for the future. The results provide an overview of the key areas of current research in the use of EO for mapping and managing wetlands, while also pointing out gaps that could hinder global inventory, assessment and monitoring of wetlands. This paper provides a summary of the main outputs with a focus on the role of EO technologies in supporting the implementation of the Ramsar Convention on Wetlands. The summary contains a qualitative analysis of the state of the art and considers possible directions and priorities for future research, development and application of EO-based technologies in wetland management. In this context we: 1) highlight those applications where EO technologies are ready for wider uptake by wetland managers, and provide suggestions for supporting such uptake; 2) indicate where EO technologies and applications currently in the research and development stages could potentially be useful in wetland management; and 3) provide recommendations for new research and development of EO technologies, that can be utilized to address aspects of wetland management not covered by the range of current EO applications.